398 Contemporary Issues in Animal Agriculture: Animal Welfare. - Tucker, C (J Anim Sci, 2018)
The Challenge. Concerns about the care of farm animals are not new. Farmers and veterinarians have long been focused on the condition of animals in their care and aim to ensure they are healthy and well nourished. In the 1960’s, the issue of whether farm animals receive humane care, that is care beyond health considerations, began to be questioned by the public. Today, key stakeholders in the conversation about animal agriculture include producers, allied industry, the corporate supply chain, and the public. Across these parties, modern-day concerns about farm animal welfare include 1) physical functioning, meaning animals should be healthy and thriving, 2) naturalness, in that animals have the ability to engage in behaviors they are highly motivated to perform, and 3) affective states, meaning that animals can experience positive states and that negative states are minimized. The emphasis placed on these concerns varies based on individual stakeholder values.The Opportunity. In the US, these concerns are primarily addressed through corporate and industry-led programs. Producer participation is either voluntary or required by a component of the supply chain. The most rigorous of these programs are audited by an independent 3rd party. However, the most productive and sustainable change also includes internal (1st or 2nd party) assessment. When combined with organizational commitment to improve animal welfare, this non-regulatory approach has a number of benefits including widespread and rapid improvements and the ability to update audit criteria on a regular basis. However, when imposed without sufficient stakeholder engagement this approach can create instability, increase the perception that animal welfare concerns are a threat to producers’ livelihoods, and fail to include key concerns of some stakeholders. The most sustainable path forward is to engage in partnership: supportive and progressive programs that address the range of modern-day animal welfare concerns.